Micro wire electro discharge grinding: optimization of material removal rate and surface roughness - Ali, Mohammad Yeakub; Abd. Rahman, Mohamed; Nordin, Rosmarina (Institute of Physics Publishing, 2017)
This paper presents the analysis and modelling of material removal rate (MRR) and surface roughness (Ra) by micro wire electro discharge grinding (micro-WEDG) with control parameter of gap voltage, feed rate, and spindle speed. The data were analyzed and empirical models are developed. The optimized values of MRR and Ra are 0.051 mm3/min and 0.25 μm respectively with 110 V gap voltage, 38 μm/s feed rate, and 1315 rpm spindle speed. The analysis showed that gap voltage has significant effect on material removal rate while spindle speed has significant effect on surface roughness.